Tessmannia princeps (Fabaceae), a new rainforest tree from the Udzungwa Mountains, Tanzania - Bianchi, Andrea; Tomasi, Laura; Mwakisoma, Aloyce; Barbieri, Matteo; Luke, Quentin (Phytotaxa, 2025)
Tessmannia princeps, a new canopy emergent rainforest tree species from the Udzungwa Mountains, Tanzania, is described and illustrated. It is a montane, unarmed tree distinguished by its large stature, extensively buttressed bole, and high number of leaflets. Tessmannia princeps shows morphological affinities with another Tanzanian species, T. densiflora, nevertheless the two species can be distinguished by morphological characters as well as by ecology and geography. A diagnostic key to the East African species of Tessmannia is provided. Due to its restricted range and small number of recorded mature individuals, the conservation status of T. princeps is assessed as Vulnerable under the IUCN criteria.